Overview Potential Predictor of Turnover Intention in Mining Company - Wina Diana Sari; Rachmayati Eka Safitri; Ahmad Hidayat; Refita Oktavyana Bahar; Cheasy Lavenia (MANAZHIM, 2023)
The turnover intention issues are detected often occur in a company, especially on employees who have competent talent and good quality work. This can cause new problems for the company if not handled properly. This study intends to look at general and specific descriptions which include potential predictors of turnover intention in mining companies. This research is aimed to all employees at PT X which is a company engaged in the mining business in Jambi province with a minimum working period of 2 years. Researchers used qualitative research by using semi-structured interviews and had been conducted by researchers to see the causal phenomenon of high turnover in the company. The interview results had then been interpreted using semantic analysis. The stages in conducting this research began with making observations which were carried out online through internet searches and interviews as an initial assessment aimed at the HR department. Research subjects are determined based on research objectives. The researcher prepared an interview guide which was conducted in person or through a zoom meeting. After the data has been collected, the researcher conducts data analysis using thematic analysis, including; understanding data, Compiling code, looking for themes. Researchers will conduct discussions related to the results of interviews and surveys that have been conducted. The output of the research is in the form of research results that will be used to improve the management of PT X's human resources. This research has a limit that is produced up to TKT 2, namely the concept of research results. Burnout, compensation, family issues and company policies are the four main themes that stand out and become a prediction that has the potential to cause turnover in PT X employees. The company should have taken steps to overcome these problems. There are many solutions to overcome the four main problems, one of which is good communication between the company, HR, and the employees themselves so as to create a win-win solution.